Novel Synthesis of Butyl (S)-2-Hydroxybutanoate, the Key Intermediate of PPARα Agonist (R)-K-13675 from Butyl (2S,3R)-Epoxybutanoate and Butyl (S)-2,3-Epoxypropanoate - Araki, Takaaki; Koura, Minoru; Yamazaki, Yukiyoshi; Shibuya, Kimiyuki (Synthesis, 2013)
Novel synthetic methods for the production of butyl (S)-2-hydroxybutanoate starting from butyl (2S,3R)-epoxybutanoate or butyl (S)-2,3-epoxypropanoate were established. The former method utilized the regioselective thiolysis of the epoxybutanoate mediated by scandium triflate and subsequent reductive cleavage of the thioether to give butyl (S)-2-hydroxybutanoate with stereochemical retention in quantitative yield. The latter method utilized one-step conversion by a combination of methylmagnesium bromide and copper catalyst in high yield.
Keywords: epoxides; regioselectivity; ring opening; Lewis acids; scandium